Simultaneously enhancing strength and ductility of carbon nanotube/aluminum composites by improving bonding conditions. (1st March 2016) - Chen, B.; Kondoh, K.; Imai, H.; Umeda, J.; Takahashi, M.
Abstract: The limited ductility of high-strength aluminum (Al) matrix composites (AMCs) reinforced with carbon nanotubes (CNTs) is a critical issue, which hinders their engineering applications. Here, we report a significantly improved ductility of CNT/Al composites with a simultaneously increased tensile strength using elevated sintering temperatures. The traditional trade-off tendency between strength and ductility is evaded in CNT/Al composites owing to concurrent improvement of Al–Al grain and CNT–Al interface bonding. The interfacial characteristics are investigated through microstructural examination and quantitative estimation using strengthening models. The study provides a strategy for fabricating CNT-reinforced metal matrix composites with high strength and good ductility. Graphical abstract: